ChemInform Abstract: New Quaternary Chalcogenides Tl18Pb2M7Q25 (M: Ti, Zr, and Hf; Q: S and Se): Crystal Structure, Electronic Structure, and Electrical Transport Properties. Issue 20 (25th April 2013) - Sankar, Cheriyedath Raj; Becker, Anna; Assoud, Abdeljalil; Kleinke, Holger
Abstract The title compounds are prepared from mixtures of the elements (1073 K, 100 h) and characterized by single crystal XRD, electrical transport measurements, and DFT calculations.